Stages of abstraction in grammar mastery - Garbačiauskienė, M. (Psichologija, 1968)
The paper analyzes the development of abstraction alongside the development of concretization. We make the presumption that that joining the opposite operation into the main one as its execution condition has an impact on the level of basic operations.Based on the absorption of grammatical concepts in 2nd, 3rd, 5th, and 7th grade, several abstraction stages imposed, i.e.) incomplete, b) formal, e) empirical, and d) logical abstraction.We concluded that the main features of grammatical concepts, meaning and form abstraction, are at different levels.
Keywords: abstraction; abstraction stages; learning grammar